The Relationship Between the Results of Osteoporosis Risk Test and Bone Mineral Density - Original Investigation - Ferda Özdemir; Derya Demirbağ Kabayel; Necdet Süt; Dilek Kurtoğlu Koçan; Şenay Demir Yazıcı; Mine Uzunali (Galenos Yayinevi, 2009)
Aim: The importance of questions for determining osteoporosis (OP) and T score; and the relation between bone mineral density (BMD) and the one-minute OP risk test which is used for evaluating the risk factors of patients for OP, were examined. Material and Methods: 206 postmenopausal women, who applied to OP clinic for the first time, were recruited. One-minute OP risk test was carried out to all patients. The answers of the questions were 'Yes' or 'No'. Having recorded from lumbar spine and femur neck by dual energy x-ray absorptiometry (DXA) the BMD values, and T scores were evaluated. Spearman correlation test, Logistic and Linear regression tests were used for the statistical analyses. Results: The question 4 (has your height shortened over 3 cm?) was statistically significant for determining the OP in femur neck (Odds ratio 3.14, %95 CI, 62-6.11). The questions 3 (have you ever taken corticosteroids over 3 months?) and 4 were significant for T score in femur neck (p<0.011, Std b=181 and p=0.027, Std b=0.157, respectively). A statistically significant negative correlation between the number of 'Yes' in the risk test and BMD in the femur neck was seen (p<0.001). No correlation was found between the result of risk test and BMD value of lumbar spine and T scores. Conclusion: The results of the one-minute OP risk test were particularly related to DXA results of femur neck. (From the World of Osteoporosis 2009;15:75-8)